Studies on the incidence and causes of infertility in goats reared under field conditions - GOEL, A K; SINHA, N K (The Indian Journal of Animal Reproduction, 2005)
The incidence of infertility (forms and causes) was studied in goats reared under field conditions. Overall incidence of infertility was 11.50%, which was of moderate degree in this species. Anoestrus and abortion were recognized as major causes leading to lowered fertility followed by repeat breeding and still birth. Goats should be allowed to reproduce after attaining 60 to 65% of adult body weight.